Answer:
the answer is B
Step-by-step explanation:
5th root of 32 = 2
5 / 5 = cancels
10 / 5 = 2
15 / 5 = 3
2xy²z³
Answer:
2xy^2z^3
Step-by-step explanation:
Given that y varies directly as x², find the percentage increase in y when x doubles.
Answer:400%
Step-by-step explanation: by the commutativity of multiplication we find (2x)^2=4(x^2)=4(y)
In one class, homework is worth 10% of the final grade, each of 3 projects is worth 20%, and a final exam is worth 30%.
(a) If a student has an 81 homework average and a 95 on the first project, what is the student's grade at this point?
(b) If the same student from part (a) gets a 72 on the second project and a 71 on the third project, what is the lowest grade the student can get on the final exam to get an 80 overall in the course?
(a) The grade at this point is_____
(Simplify your answer. Round to the nearest tenth as needed.)
(b) The lowest possible grade is____
(Simplify your answer. Round to the nearest integer as needed.)
a) At this point, the grade is 27.1
b) The lowest possible grade is 81
How to get the grades of the student?
a) At this point the student has 81 in homework and 95 on the first project.
Remember that the homework is worth 10% of the final grade, and each project is worth 20%, then at this point the final grade is:
F = 0.10*81 + 0.20*95 = 27.1
b) The student gets 72 on the second project and 71 on the third project, at this point the final grade is:
F = 27.1 + 0.20*72 + 0.20*71 = 55.7
Now the student wants to get a final grade of 80, then if we define x as the grade on the final exam (which is worth 30%) we must have that:
55.7 + 0.30*x = 80
Now we can solve this for x:
x = (80 - 55.7)/0.30 = 81
The lowest possible grade that he must get is 81.
If you want to learn more about percentages:
https://brainly.com/question/843074
#SPJ1
Suzy invests $2,600 in an account that earns 2.3% annual interest, compounded continuously. What is the value of the account after 10 years? Round to the nearest dollar
Answer:
$3,272
Step-by-step explanation:
Continuous Compounding Formula
[tex]\large \text{$ \sf A=Pe^{rt} $}[/tex]
where:
A = Final amountP = Principal amounte = Euler's number (constant)r = annual interest rate (in decimal form)t = time (in years)Given:
P = $2,600r = 2.3% = 0.023t = 10 yearsSubstitute the given values into the formula and solve for A:
[tex]\sf \implies A=2600e^{(0.023 \times 10)}[/tex]
[tex]\sf \implies A=2600e^{0.23}[/tex]
[tex]\implies \sf A=3272.360026...[/tex]
Therefore, the value of the account after 10 years is $3,272 to the nearest dollar.
find the positive square root of 217.05 and 100.2001......with division method
The square root of 217.05 is 14.73 and the square root of 100.2001 is 10.01.
How to depict the square root?It should be noted that square root is factor of a number that when multiplied by itself will give the original number.
In this case, the square root of 217.05 is 14.73 and the square root of 100.2001 is 10.01.
Learn more about square root on:
brainly.com/question/428672
#SPJ1
PLS HELP I DONT KNOWWW!!
Answer:
3rd option
Step-by-step explanation:
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
calculate m using the slope formula
m = [tex]\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex]
with (x₁, y₁ ) = (0, - 2) and (x₂, y₂ ) = (4, - 1) ← 2 points on the line
m = [tex]\frac{-1-(-2)}{4-0}[/tex] = [tex]\frac{-1+2}{4}[/tex] = [tex]\frac{1}{4}[/tex]
the line crosses the y- axis at (0, - 2 ) ⇒ c = - 2
y = [tex]\frac{1}{4}[/tex] x - 2 ← equation of line
Find the value of x ??
A. 31
B. 5
C. 11
D. 25
Answer: 11
Step-by-step explanation:
By the trapezoid midsegment theorem, x = (9+13)/2 = 11
In 1990, the average monthly bill for cellular telephone service was $80.90. From 1990-1997, the monthly bill decreased by 8.6% per year (in other words, each year the bill is 91.4% of
what is was the previous year (Source: Statistical Abstract of the United States).
Part a: Write a formula for the average monthly cellular telephone bill in terms of the year. Let n = 1 represent 1990.
Part b: What was the average monthly bill in 1993
A)The formula for the average monthly cellular telephone bill in terms of the year will be A = 80.90(0.914)ⁿ⁻¹
B)The average monthly bill in 1993 willl be $ 61.77
What is the percentage?The quantity of anything is stated as though it were a fraction of a hundred. A fraction of 100 can be used to express the ratio.
The formula for the average monthly cellular telephone bill in terms of the year willl be,
A=P(R/100)ⁿ
A = 80.90(0.914)ⁿ⁻¹
The average monthly bill in 1993 is found as ;
n=4 for 1993
A=P(R/100)ⁿ
A = 80.90(0.914)³⁻¹
A=$ 61.77
Hence the formula for the average monthly cellular telephone bill in terms of the year will be A = 80.90(0.914)ⁿ⁻¹ and the average monthly bill in 1993 willl be $ 61.77.
To learn more about percentages, refer to:
https://brainly.com/question/13450942
#SPJ1
Please help due tomorrow
What transformations could have been used to map ABCE onto A’B’C’D’E?
Answer: This looks like it is a reflection of the y-axis and then an enlarging dilation.
30.
10 cm
O
7 cm
10 cm
4 cm
How many triangles are needed to draw the net of this object?
There are two triangles in the figure(triangular prism) option third is correct.
What is a triangular prism?When a triangle is, stretch it out to produce a stack of triangles, one on top of the other. A triangular prism is a name given to this novel 3D object.
The complete question is:
How many triangles are needed to draw the net of this object?
4321For the figure please refer to the attached picture.
As we can see in the figure we have given a triangular prism:
The triangular prism has two triangles.
A triangle for the base of the prism and a triangle for the top of the prism.
The lateral faces of the prism are rectangular.
Thus, there are two triangles in the figure(triangular prism) option third is correct.
Learn more about triangular prisms here:
brainly.com/question/16909441
#SPJ1
what is the length of the base? help me please thank u ;)
=============================================================
Explanation:
a = 26 and b = 26 are the congruent legs
angle C = 60 degrees is between sides 'a' and b
c = unknown base which is opposite angle C
We'll use the law of cosines to find this missing side.
c^2 = a^2 + b^2 - 2*a*b*cos(C)
c^2 = 26^2 + 26^2 - 2*26*26*cos(60)
c^2 = 676
c = sqrt(676)
c = 26
It turns out that all three sides are the same length (26), which means this isosceles triangle is really equilateral. Consequently, it means all three interior angles are 60 degrees each.
---------------
Here's another way to see why we have an equilateral triangle.
The vertex angle is 60 degrees. Let x be the measure of each base angle. Those two base angles add to the 60 degrees to get 180
x+x+60 = 180
2x+60 = 180
2x = 180-60
2x = 120
x = 120/2
x = 60
Each base angle is 60 degrees, so all three angles are 60 degrees. This points us to the triangle being equilateral and we can say all three sides are 26 units long.
If we didn't have an equilateral triangle, then we'd have no choice but to use the law of cosines mentioned earlier.
[tex]\quad \huge \quad \quad \boxed{ \tt \:Answer }[/tex]
[tex]\qquad \tt \rightarrow \:base \:\:side = 26 \:\: units [/tex]
____________________________________
[tex] \large \tt Solution \: : [/tex]
As the two sides of the triangle are equal, the corresponding angles opposite to the the sides are equal as well.
[tex] \textsf{let each of those angles measure ' x ' } [/tex]
[tex]\qquad \tt \rightarrow \:x + x + 60 = 180[/tex]
[ sum of all interior angles of a triangle ]
[tex]\qquad \tt \rightarrow \:2x + 60 = 180[/tex]
[tex]\qquad \tt \rightarrow \:2x = 180 - 60[/tex]
[tex]\qquad \tt \rightarrow \:2x = 120[/tex]
[tex]\qquad \tt \rightarrow \:x = \cfrac{120}{2} [/tex]
[tex]\qquad \tt \rightarrow \:x = 60 \degree[/tex]
Therefore, all angles of the triangle are equal. that being the case we can conclude that it's an equilateral triangle.
henceforth, all its sides are equal to one another.
[tex]\qquad \tt \rightarrow \:base \: \: side = \: \: 26 \: \: units[/tex]
How tall is the tree?
5ft
35°
-20ft-
[? ]ft
Answer:
[tex]\boxed{\bf 19ft}[/tex]Step-by-step explanation:
[tex]\bf tan\:\theta =\cfrac{opp}{adj}[/tex]
[tex]\bf tan(35^o)=\cfrac{x}{20}[/tex]
[tex]\bf 20\;tan (35^o)=x[/tex]
[tex]\bf 14ft=x[/tex]
The height of the tree:-
[tex]\bf x+5ft[/tex][tex]\bf 14ft+5ft[/tex][tex]\bf 19ft[/tex]Answer:
19.00 ft to the nearest hundredth.
Step-by-step explanation:
tan 35 = h / 20
h = 20 tan 35
Now we add the man's height
Total height of the tree
= 20 tan 35 + 5
= 19.00 ft to the nearest hundredth.
Does this graph show a function? Explain how you know.
Answer:
No, the graph fails the vertical line test
Step-by-step explanation:
To determine if the graph is a function, we can use the vertical line test.
Use a vertical line, if the vertical passes through two or more points, the graph is not a function
Looking at the y axis ( which is a vertical line), it passes through two points
This means the graph is not a function
No, the graph fails the vertical line test
What’s the answer? How do I find the opposite
Answer:
I think the answer is 4
Step-by-step explanation:
The function y = f(x) is graphed below. What is the average rate of change of the
function f(x) on the interval -3 ≤ x ≤-1?
The average rate of change of the function in the given interval -3 ≤ x ≤-1 is 10.
What is the average rate of change?The average Rate of Change of the function f(x) can be calculated as;
[tex]f(x) = \dfrac{f(b) - f(a)}{b-a}[/tex]
Interval -3 ≤ x ≤-1
a = -3, b = -1
f(a) = f(-3) = -20
f(b) = f(-1) = 0
Step 2: Find Average
[tex]f(x) = \dfrac{f(b) - f(a)}{b-a}\\\\\\f(x) = \dfrac{f(-1) - f(-3)}{-1-(-3)}\\\\\\f(x) = \dfrac{0 - (-20)}{2}\\\\f(x) = 10[/tex]
Therefore, the average rate of change of the function in the given interval -3 ≤ x ≤-1 is 10.
Learn more about average rate;
https://brainly.com/question/20784578
#SPJ1
please answer I've got 10 mins
100 POINTS FOR BRAINLIEST
Determine if the two expressions are equivalent and explain your reasoning.
3(4n) + 2 + 6n and 13n + 2
Answer:
3(4n) + 2 + 6n
12n + 2 + 6n
12n + 6n + 2
18n + 2 is not equal to 13n + 2
hence both the expression are not equivalent
What is the function written in vertex form? f(x) = 4(x 6)2 10 f(x) = 4(x 6)2 – 26 f(x) = 4(x 6)2 – 134 f(x) = 4(x 6)2 154
The required vertex form of the given equation is a) [tex]4(x-6)^2 +10[/tex] is correct
the function [tex]y=4x^2+24x+154[/tex] is given,
vertex form of a equation [tex]y=ax^2+bx+c[/tex] is given by [tex]y=a(x-h)^2+k[/tex].
since [tex]y=4x^2+24x+154[/tex]
Now h = - b/2a
h = -N
Now at x = 0
k = 10
vector form can be given by [tex]4(x+6)^2 +10[/tex]
The question is incomplete. The question could be:
what is the correct vertex form of equation [tex]y=4x^2+24x+154[/tex]?
a)[tex]4(x+6)^2 +10[/tex]
b)[tex]4(x-6)^2 -26[/tex]
c)[tex]4(x-6)^2 -134[/tex]
d)[tex]4(x-6)^2 +154[/tex]
Thus, the vector form of the given function is [tex]4(x+6)^2 +10[/tex]
learn more about vector form here:
https://brainly.com/question/13921516
#SPJ1
Helppp! Which linear inequality is represented by the graph
Need help simple explanation if possible
Answer: 21 sqrt(43)/43
Step-by-step explanation: The tangent identity states that tanx = sinx/cosx. Thus, we get 21/22 / sqrt(43)/22. We can simplify this to 21 sqrt(43)/43
Please mark my answer as brainliest if this helped you.
Write [tex]\frac{1}{22}[/tex] as a decimal, Also please include the working out plus anyone that includes other examples will be given brainlest!
Thank you!
Do long division (see the attachment).
[tex]\dfrac{1}{22}=0.04545\ldots=0.0\overline{45}[/tex]
how to solved theses question (4.2×7)-10.4÷2²+2.9×3-6 explain
Answer:
29.5
Step-by-step explanation:
Use PEDMAS
P - Paraenthesis
E -Exponents
D - Divsion
M - Multiplication
A and S - Addition and subtraction respectively.
First multiply 4.2 and 7 as they are inside the parenthesis
Then find 2² which 4
(4.2 *7) - 10.4 *2² + 2.9*3 - 6 = 29.4 - 10.4 ÷2² + 2.9*3 - 6 {Parenthesis}
= 29.4 - 10.4÷4 + 2.9*3 - 6 {Exponents}
= 29.4 - 2.6 + 2.9*3 - 6 {Division}
= 29.4 - 2.6 + 8.7 - 6 {Multiplication}
= 29.5
A circle inside of a square. The square has side lengths of 5 meters.
Tariq also designs hot tubs. The diameter of the hot tub is 3 meters. What is the area of the deck that surrounds the hot tub? If necessary, round to the nearest tenth.
Answer:
the area is 25/4 π
Step-by-step explanation:
diameter is 5 m
area will be 25/4π
Answer:
17.9 m²
Step-by-step explanation:
The area of the deck is the difference between the area of the square and the area of the circular hot tub.
__
square areaThe area of the square is given by the formula ...
A = s² . . . . where s is the side length
For a side length of 5 m, the area is ...
A = (5 m)² = 25 m²
circle areaThe area of a circle is found from the formula ...
A = (π/4)d² . . . . where d is the diameter
For a diameter of 3 m, the area is ...
A = (π/4)(3 m)² = 9/4π m² ≈ 7.069 m²
deck areaThe area of the deck is the difference between the square area and the circle area:
deck area = 25 m² -7.069 m² ≈ 17.9 m²
The area of the deck surrounding the hot tub is about 17.9 m².
The function a(b) relates the area of a trapezoid with a given height of 14 and one base length of 5 with the length of its other base. It takes as input the other base value, and returns as output the area of the trapezoid. a(b)=14 x b+5/2
A function assigns the values. The inverse of the function in terms of the area will be b=(a/7)-5.
What is a Function?A function assigns the value of each element of one set to the other specific element of another set.
The complete question is,
The function a(b) relates the area of a trapezoid with a given height of 14 and one base length of 5 with the length of its other base. It takes as input the other base value, and returns as output the area of the trapezoid. a(b)=14 x b+5/2. Write a function in terms of area to find the length of the other side.
The given is the function of the area of the trapezoid, a(b)=14 x b+5/2.
The area of a trapezoid is given as,
Area = Height × [(Sum of parallel sides)/2]
The given function can be written in terms of area as,
[tex]a = 14\times \dfrac{(b+5)}{2}\\\\\dfrac{2(a)}{14} = b+5\\\\\dfrac{2(a)}{14} -5= b\\\\\dfrac{(a)}{7} -5= b[/tex]
Hence, the inverse of the function in terms of the area will be b=(a/7)-5.
Learn more about Function:
https://brainly.com/question/5245372
#SPJ1
state one example of 2 numbers where the LCM of the 2 numbers is the product of those numbers. explain your answers
Answer:
See below
Step-by-step explanation:
3 and 5 have a LCM of 15 which is 3 * 5
Need help (pic included)
Answer:
a = 1Step-by-step explanation:
We have the expression:
12x² + ax - 20
3x + 4 is a factor. Therefore:
12x² + ax - 20 = (3x · 4x) + ax + (4 · (-5))
12x² + ax - 20 = (3x + 4)(4x - 5)
(3x + 4)(4x - 5) = (3x)(4x) + (3x)(-5) + (4)(4x) + (4)(-5)
= 12x² - 15x + 16x - 20 = 12x² + x - 20
a = 1Other method:12x² + ax - 20 = (3x + 4)(bx + c)
12x² + ax - 20 = (3x)(bx) + (3x)(c) + (4)(bx) + (4)(c)
12x² + ax - 20 = 3bx² + 3cx + 4bx + 4c
12x² + ax - 20 = 3b² + (3c + 4b)x + 4c
therefore
3b = 12
a = 3c + 4b
4c = -20
3b = 12 ⇒ b = 4
4c = -20 ⇒ c = -5
substitute to a:
a = 3 · (-5) + 4 · 4
a = -15 + 16
a = 1Find the length of side BC.
Give your answer to 3 significant figures.
C
A
71°
B
Answer:
BC ≈ 19.4 cm
Step-by-step explanation:
using the cosine ratio in the right triangle
cos71° = [tex]\frac{adjacent}{hypotenuse}[/tex] = [tex]\frac{AB}{BC}[/tex] = [tex]\frac{6.3}{BC}[/tex] ( multiply both sides by BC )
BC × cos71° = 6.3 ( divide both sides by cos71° )
BC = [tex]\frac{6.3}{cos71}[/tex] ≈ 19.4 cm ( to 3 sig. figs )
Answer:
19.4°
Step-by-step explanation:
I put the image of how I did it if you don't understand let me know
In ABC, CT is a median. What is the measure of AB?
Fill in the blank by enter in just a number for your answer.
Answer:
AB = 102
Step-by-step explanation:
the median CT bisects the side AB at T , then
BT = AT , that is
7x + 9 = 5x + 21 ( subtract 5x from both sides )
2x + 9 = 21 ( subtract 9 from both sides )
2x = 12 ( divide both sides by 2 )
x = 6
then
AB = 5x + 21 + 7x + 9 = 12x + 30 = 12(6) + 30 = 72 + 30 = 102
The measure of AB is 102.
How to estimate the measure of AB?
The median CT bisects the side AB at T, then
BT = AT
7x + 9 = 5x + 21
subtracting 5x from both sides of the equation, we get
2x + 9 = 21
subtract 9 from both sides, and we get
2x = 12
Divide both sides by 2, we get
x = 6
then, AB = 5x + 21 + 7x + 9
AB = 12x + 30
Substituting the value of x,
12x + 30 = 12(6) + 30
= 72 + 30
AB = 102
Therefore, the measure of AB is 102.
To learn more about triangles
https://brainly.com/question/11070154
#SPJ2
You are walking directly away from your house.
You are 5 miles away from your house when
you start walking, so you can determine your
distance from your house by adding 5 to the
number of miles you have walked. In the
equation below, a represents the number of
miles you have walked, and y represents your
distance from home in miles.
The relationship between these two variables
can be expressed by the following equation:
y = x + 5
Identify the dependent and independent
variables.
Your distance
from home
Number of
miles you
walk
Dependent
variable
Independent
variable
Answer:
dependent: your distance from home
independent: number of miles you walk
Step-by-step explanation:
lmk if you want an explanation
Dilate the figure by the scale factor. Then enter the new coordinates.
K= 2
Answer:
A(2, 8)
B(4, 4)
C(-4, 2)
Step-by-step explanation:
Multiply all the coordinates by 2
Which is equivalent to 3√8* ?
O x √8^3
O 8 ^3/x
O 8 ^x/3
O 8^3x
Answer:
O 8 ^x/3
Step-by-step explanation:
Remember that :
[tex]\sqrt[n]{x} = x^\frac{1}{n}[/tex]
………………………………
Then
[tex]\sqrt[n]{8^x} = (8^{x})^{\frac{1}{3}}[/tex]
[tex]= 8^{x\times\frac{1}{3}[/tex]
[tex]=8^{\frac{x}{3}[/tex]
solution.
5(4x + 7)-2x = ________+ 21
Answer:
18x + 14
Step-by-step explanation:
First, we need to distribute the 5:
5(4x + 7) - 2x = __ + 21
20x + 35 - 2x = __ + 21
Now, we can combine like terms:
20x + 35 - 2x = ___ + 21
18x + 35 = ___ + 21
> subtract 21 from both sides to isolate "___"
18x + 35 = __ + 21
-21 -21
18x + 14 = ___
now that we have a solution, we should check that it works:
5(4x + 7) - 2x = ____ + 21
5(4x + 7) - 2x = 18x + 14 + 21
{simplify both sides:}
20x + 35 -2x = 18x + 35
18x + 35 = 18x + 35
(TRUE)
So, we know our solution is 18x + 14
hope this helps!!